Manpower Allocation with Time Windows and Job-Teaming Constraints - LI, Yanzhi (Institutional Knowledge at Singapore Management University, 2005)
In this work, we study manpower allocation with time windows and job-teaming constraints. A set of jobs at dispersed locations requires teams of different types of workers where each job must be carried out in a preestablished time window and requires a specific length of time for completion. A job is satisfied if the required composite team can be brought together at the job's location for the required duration within the job's time window. The objective is to minimize a weighted sum of the total number of workers and the total traveling time. We show that construction heuristics used with simulated annealing is a good approach to solving this NP-hard problem. In experiments, this approach is compared with solutions found using CPLEX and with lower bounds obtained from a network flow model.